2021
DOI: 10.1186/s13071-021-05069-7
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus and temperature modulate Elizabethkingia anophelis in Aedes albopictus

Abstract: Background Vector-borne pathogens must survive and replicate in the hostile environment of an insect’s midgut before successful dissemination. Midgut microbiota interfere with pathogen infection by activating the basal immunity of the mosquito and by synthesizing pathogen-inhibitory metabolites. Methods The goal of this study was to assess the influence of Zika virus (ZIKV) infection and increased temperature on Aedes albopictus midgut microbiota. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 89 publications
2
30
0
Order By: Relevance
“…aegypti. Also, the number of bacterial ASVs shared by all groups for females (19) and males (24) was lower than the total number of bacterial ASVs for females (42) and males (71), suggesting a small core bacterial community that was not altered by the presence of MPs in the gut.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…aegypti. Also, the number of bacterial ASVs shared by all groups for females (19) and males (24) was lower than the total number of bacterial ASVs for females (42) and males (71), suggesting a small core bacterial community that was not altered by the presence of MPs in the gut.…”
Section: Discussionmentioning
confidence: 95%
“…Elizabethkingia anophelis has been demonstrated to affect Plasmodium development in Anopheles mosquitoes and Zika virus infection rates in Ae. albopictus [42,43] . Elizabethkingia density changes as the result of MP ingestion suggests the potential for MPs to indirectly affect arbovirus transmission by Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti with experimental ZIKV infection have found associated bacterial taxa such as the families Rhodobacteraceae and Desulfuromonadaceae and the genera Cellulosimicrobium, Elizabethkingia, Enterobacter, Pseudomonas, and Staphylococcus ; in Ae. albopictus , Elizabethkingia anophelis was associated with ZIKV infection [ 25 , 84 , 96 ]. Additionally, E. anophelis and Lysinibacillus reduced ZIKV infection, affecting vector competence [ 84 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…albopictus , Elizabethkingia anophelis was associated with ZIKV infection [ 25 , 84 , 96 ]. Additionally, E. anophelis and Lysinibacillus reduced ZIKV infection, affecting vector competence [ 84 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…inhibits viral and parasite infection in A. aegypti cells and A. gambiae mosquitoes through protease or depsipeptide synthesis [61,62]. It was already shown that Elizabethkingia anophelis , a bacterium of the phylum Bacteroidetes, artificially fed to A. albopictus reduces ZKV infection rates [63]. On the other hand, Serratia odorifera gut colonization increases A. aegypti susceptibility to Dengue virus infection [64], Penicillium chrysogenum fungus facilitates A. gambiae infection with Plasmodium via up-regulation of an arginine digestion enzyme preventing the production of nitric oxide, a known microbicidal radical [65].…”
Section: Discussionmentioning
confidence: 99%